KORELASI ANTARA PERSEPSI DAN HASIL BELAJAR SISWA TERHADAP PELAKSANAAN KEGIATAN PEMBELAJARAN PENDIDIKAN JASMANI DI SDN 120 REJANG LEBONG - Marwiyah Marwiyah (LP4MK STKIP PGRI Lubuklinggau, 2023)
The background of this research is the Perceptions of Grade 4, 5 and 6 Students in the physical health and recreation education subject at SDN 120 Rejang Lebong. Due to the many differences in understanding, motivation, and perception of each individual. To find out student perceptions, researchers conducted indicators, such as internal factors including learning process, motivation, and personality. While external factors include, intensity, size, opposites, repetition, movement and new things. This research is descriptive survey research. The population is 43 students. Samples taken 35 students with the sampling technique that is random sampling. The instrument used is a closed questionnaire, and from its shape it is included in the rating scale questionnaire. Using a Likert Scale score. The results showed that the perceptions of students in grades 4, 5 and 6 in Penjaskesrek learning in the very good category were 18 students (61%), the good category was 11 students (39%), the category was quite good 5 students (19%), the category was not good a number 3 students (13%). It can be concluded that the perceptions of students in grades 4, 5 and 6 in learning Physical Education Health and Recreation are in the very good category, and the learning outcomes obtained by students in grades 4, 5 and 6 have an average score of 80.21 in the very good category.